Uncomplicated Acute Renal Failure and Post-Hospital Care: A Not So Uncomplicated Illness - Fischer, Michael J. (S. Karger AG, 2008)
BACKGROUND: Although uncomplicated acute renal failure (ARF) is associated with significant hospital resource utilization, its health care requirements following hospital discharge are not well understood. The goal of this study was to characterize the post-hospital care requirements incurred by patients with uncomplicated ARF and to determine its important influencing factors. METHODS: We obtained hospital case mix data sets for a 2-year period (1999–2000) from the Massachusetts Division of Health Care Finance and Policy. Utilizing DRG and ICD-9-CM codes from 23 Massachusetts hospitals, we identified 2,128 adult patients whose primary reason for hospitalization was uncomplicated ARF. Post-hospital care was defined as the receipt of extended facility care or home health care following hospital discharge. RESULTS: Nearly 50% of patients hospitalized with uncomplicated ARF required some type of post-hospital care, of whom 27% underwent extended facility care while 22% received home health care. The post-hospital care requirements for uncomplicated ARF were similar to those for serious medical conditions (e.g. heart failure) and exceeded those of many common illnesses (e.g., bronchitis). Advancing age, worsening severity of illness, female gender, and emergency room admission were independently associated with receipt of post-hospital care (p < 0.05). A trend existed between less frequent post-hospital care requirements and hospitalization at academic medical centers compared with non-academic hospitals. CONCLUSIONS: Uncomplicated ARF is frequently associated with prolonged care following hospitalization. As the health care utilization for ARF becomes better characterized, these post-hospital care resources should not be overlooked.